(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The aim of the study was to determine the job satisfaction levels of the personnel who worked in sports organization. 285 randomly selected people who worked in sports organization participated in this study. A form for personal information and Minnesota Job Satisfaction Scale (MSQ) developed by Weiss et al (1967) and checked for validity and reliability by Baycan (1985) were used in the study. Mann-Whitney U, Kruskal-Wallis H and Dunns multiple comparison tests were used for the analysis of the data. A significant difference was found among the groups in terms of their job satisfaction scores with increasing age in the statement of wages earned for the profession. Satisfaction levels in terms of wages showed significant difference as the educational levels of personnel decreased. It was stated that the personnel whose job satisfaction levels were generally moderate were not pleased in terms of payment and the chances for advancement. However, the personnels job satisfaction scores being moderate shows that payment alone does not affect job satisfaction.